2008
DOI: 10.1111/j.1365-2095.2008.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Organs development, gene expression and health of Atlantic salmon (Salmo salarL.) fed genetically modified soybeans compared to the near-isogenic non-modified parental line

Abstract: The present experiment was conducted to study the possible effects of genetically modified (GM), full-fat soybean meal (FFSBM) from Round-up Ready Ò soybeans compared to its parental, and closest near-isogenic, non-modified (nGM) soybean variety, added at moderate (150 g kg )1 ) and high (300 g kg )1 ) inclusion levels. The fish showed a high specific growth rate (SGR 1.27-1.52), and nearly doubled their body weight (BW), with final weights varying from 1009 to 1110 g. Increased levels of dietary FFSBM, indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 59 publications
5
31
1
Order By: Relevance
“…The immunology results support those of Sagstad et al (2008) and likely indicate a lack of adverse health effects from the inclusion of fermented soybean meal in Rainbow Trout diets. Although PSG contains possible probiotic microbes (Gatesoupe 1999), the innate immune response in the fish fed PSG showed no major responses.…”
Section: Discussionsupporting
confidence: 74%
“…The immunology results support those of Sagstad et al (2008) and likely indicate a lack of adverse health effects from the inclusion of fermented soybean meal in Rainbow Trout diets. Although PSG contains possible probiotic microbes (Gatesoupe 1999), the innate immune response in the fish fed PSG showed no major responses.…”
Section: Discussionsupporting
confidence: 74%
“…However, the increase in LER was minor. In salmon it is found that PER correlated positively with LER (Sagstad et al, 2008), in agreement with the present study. Which of the two factors, LPV or LER, give the more accurate answer depends on several factors; LPV depends on more steps in analytical procedures and is calculated from the fat amount in the biomass increase, while LER is calculated from the total biomass increase, also discussed by Lie et al (1988).…”
Section: Protein and Fat Utilizationsupporting
confidence: 82%
“…Except for the magnitude, they were generally in line with results of previous studies with SBM in diets for older salmonids [11], [28], [33], [46]. Nevertheless, and in contrast to many studies with older salmonids [28], [33], [47][48], survival and growth performance of the SBM-fed juvenile salmon was enhanced, the cause of which is not clear. However, some studies indicate that low levels of saponins can stimulate growth [49][52], suggesting that the present positive effect of SBM may be due to its content of saponins.…”
Section: Discussionsupporting
confidence: 84%